Condition number of the matrix of transition to the normal Jordan form - Grabovskii, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish necessary and sufficient conditions for the well-conditioned reduction of a matrix to the Jordan normal form.